Depth‐dependent detritus production in the sponge, Halisarca caerulea. (4th December 2019) - Lesser, Michael P.; Mueller, Benjamin; Pankey, M. Sabrina; Macartney, Keir J.; Slattery, Marc; de Goeij, Jasper M.
Abstract: Sponges are important ecological and functional components of coral reefs. Recently, a new hypothesis about the functional ecology of sponges in organic matter recycling pathways, the sponge‐loop hypothesis, in which dissolved and particulate organic matter is taken up by sponges and shunted to higher trophic levels as detritus, has been proposed and demonstrated for shallow (< 30 m) cryptic species. However, support for this hypothesis at mesophotic depths (∼ 30–150 m) is lacking. Here, we examined detritus production, a prerequisite of the sponge loop pathway, in a reciprocal transplant experiment, using Halisarca caerulea from water depths of 10 and 50 m. Detritus production was significantly lower in mesophotic sponges compared to shallow samples of H. caerulea . Additionally, detritus production rates in transplanted sponges moved in the direction of rates observed for resident conspecifics. The microbiome of these sponge populations was also significantly different between shallow and mesophotic depths, and the microbial communities of the transplanted sponges also shifted in the direction of their new depth in 10 d largely driven by changes in Oxyphotobacteria, Acidimicrobiia, Nitrososphaeria, Nitrospira, Deltaproteobacteria, and Dadabacteriia . This occurred in an environment where the availability of both dissolved and particulate trophic resources changed significantly across the shallow to mesophotic depth gradient where these sponge populations were found. These results suggest that changes in sponge detritus production are primarily driven by differential quality and quantity of trophic resources, as well as their utilization by the sponge host, and its microbiome, along the shallow to mesophotic depth gradient.